(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, cotton is used in the sowing of the republic with the use of a sprayer mounted on a cultivator KHU-4 when spraying the suspension between rows of plants. Field test results are provided that ensure that the leaves are organized and that the leaves are covered with a chemical mixture